Exploring of some benzoquinone derivatives impact on Acetylcholinesterase enzyme activity - Hatice Duran (German Journal of Pharmaceuticals and Biomaterials)
The discovery of acetylcholinesterase inhibitors is important for the treatment of Alzheimer's disease, which is the most common type of dementia. Due to the side effects of commonly used acetylcholinesterase inhibitors, studies aimed at discovering new inhibitors are increasing. Therefore, in this study, the effects of some benzoquinone derivatives, 1,4-benzoquinone (1a), 2,6-dichloro-1,4 benzoquinone (1b), and 2,6-dimethyl-1,4-benzoquinone (1c) on AChE enzyme were investigated. In vitro studies were conducted to understand the possible inhibition mechanism in the interaction of enzyme-benzoquinone compounds, and the effects of these compounds were examined. The quinones examined were found to exhibit effective inhibition of the AChE enzyme. IC50 values were determined to be 48-187 nM, and KI values ranged from 54 ± 0.007 nM to 262 ± 0.016 nM. These benzoquinones exhibited different inhibition mechanisms. While 1,4-benzoquinone (1a) and 2,6-dimethyl-1,4-benzoquinone (1c) showed competitive inhibition effects, 2,6-dichloro-1,4-benzoquinone (1b) exhibited noncompetitive inhibition effects. Additionally, among the compounds whose effects were examined, 2,6-dimethyl-1,4-benzoquinone (1c) showed the most effective inhibitor property with the lowest KI value. The findings will add to the body of knowledge on creating fresh, potent, and successful treatment approaches.